The EU emissions trading scheme allowance prices, trade flows, competitiveness effects - Gernot Klepper; Sonja Peterson (Fondazione Eni Enrico Mattei (FEEM), 2004)
The upcoming European Emissions Trading Scheme (ETS) is one of the more controversial climate policy instruments. Predictions about its likely impact and its performance can at present only be made to a certain degree. As long as the National Allocations Plans are not finally settled the overall supply of allowances is not determined. In this paper we will identify key features and key impacts of the EU ETS by scanning the range of likely allocation plans using the simulation model DART. The analysis of the simulation results highlights a number of interesting details in terms of allowance trade flows between member countries, of allowance prices, and in terms of the role of the accession countries in the ETS.
Keywords: F18; Q48; D58; Q54; 330; Kyoto targets; Computable general equilibrium model; DART; EU Emissions trading scheme; Klimaschutz; Emissionsrechte; Preis; Allgemeines Gleichgewicht; Simulation; EU-Staaten